1258 Computational Modelling Of 3D Printed Scaffolds for Heart Valve Regeneration. (12th October 2021) - Georgi, M; Wu, L; Ma, H; Hamilton, G; Song, W
Abstract: Aim: Prosthetic heart valve replacement remains the gold standard treatment for valvular heart disease. However, its durability is limited and there is thus a need to develop an understanding of the feasibility of alternative replacement therapies. 3-dimensional printing of heart valves has been explored due to its patient-specific design and control of desired biomechanical properties. Computational studies of the synthetic valves will contribute to optimisation of designs, as well as improved understanding of the biomechanical behaviour of the complex structures. Method: Aortic valve dimensions at an average of 100mmHg were used for the computerised design of the valves. Fine Element Analysis modelling generated computational experiments alongside predicted results. Simulated radial pressures tests were conducted at pressures from 0mmHg to 140mmHg and compression tests were conducted at displacement levels between 0-10mm. A Young's modulus of 0.5 MPa was used. All simulations were conducted in a quasi-static manner. Results: As the radial pressure on the valves increased, the Mises stresses increased. The maxium Mises stress of the heart valve was 0.09MPa and 0.13MPa under the pressures of 90mmHg and 140mmHg respectively. As valve displacement increased, the Mises stress of the heart valves proportionally rose. In simulated radial pressures tests, the compressive force was 0.19N at 1mm compressive displacment and 1.8N at 10mm compressive displacment. Conclusions: The simulations demonstrated that 3D-printed heart valve scaffolds can withstand simulated radial pressure and compression tests. A further mechanical tests of the printed scaffold and understanding of its response to hemodynamic dynamic flow is required for the continuity of further study.